IMPROVEMENT IN THE APPROACHES TO THE TREATMENT OF EMIGRANTS AND RE-EMIGRANTS WITH DEPRESSIVE DISORDERS - Venger, O. P.; Mysula, Yu. I. (International Journal of Medicine and Medical Research, 2017)
Background. Social and clinical relevance of emigration and re-emigration is determined by a significant amount of Ukrainians that emigrate and re-emigrate. Clinical features of depressive disorders have not been studied; as well as risk factors and antiriscs of various forms of depression have not been established yet. Development of comprehensive approaches to the treatment and rehabilitation of these patients is an effective way of resolving of this problem and is of significant scientific, practical, medical and social importance. Objective. The development of measures for treatment of depressive disorders in emigrants and re-emigrants is based on investigation and analysis of clinical-psychopathological phenomenology of depression. Methods. We examined 196 emigrants, 191 re-emigrants and 198 not emigrants with final clinical diagnosis of depressive disorder according to ICD-10 criteria. Examination was conducted by means of depression rate according to M. Hamilton, the Montgomery-Asberg and Symptom Checklist-90-Revised and the scale of life quality by WHO QOL-26. Statistical analysis of the results was performed using nonparametric methods: Mann-Whitney test, Wilcoxon criterion of signs. Results. It was found that the maximum content of organic acids is accumulated in grass Hyssopus officinalis L. (Lamiaceae), and the minimal is in the leaves of Chrysánthemum xhortorum L. variety Apro (Asteraceae). The dominance of aliphatic acids was determined by means of gas chromatography. Benzoic is predominant among aromatic acids. Conclusions. The suggested therapy schemes proved higher effectiveness compared with the traditional one, and also allowed to improve the life quality of emigrants and re-emigrants.